The effect of workplace environment on coal miners' gut microbiota in a mouse model - Li, Lei; Zhi, Mei; Wang, Siwei; Deng, Jun; Cai, Qing; Feng, Dayun (Frontiers in Microbiology, 2024)
The coal mine workplace environment is a significant factor in inducing occupational health issues, such as intestinal dysfunction in coal miners. However, the mechanism by which the coal mine workplace environment induces intestinal dysfunction is still unclear. Therefore, we applied the Coal Mine Workplace Environment Biological Simulation (CEBS) model which was previously constructed to detect the intestinal pathological manifestations and changes in the gut microbiota of mice from the perspectives of intestinal function, tissue morphology, and cell molecules. CEBS mice showed increased fecal water content, shortened colon length, significant activation of MPO+ and CD11b+ numbers, and significant changes in IL-1b, IL-6, and IL-12 expression levels. In addition, we also found an imbalance in the proportions of Firmicutes, Bacteroidetes, Lactobacillus, and Parabacteroides in CEBS mice, resulting in significant changes in gut microbial diversity. After intervention with compound probiotics, the intestinal function of CEBS + Mix mice was improved and inflammation levels were reduced. Results indicated that stress in the coal mine workplace environment can lead to intestinal dysfunction and inflammatory damage of the colon and use of compound probiotics can improve intestinal dysfunction in CBES mice. In our study, we revealed that there is a correlation between coal mine workplace environment and diversity disorders of gut microbiota. This discovery has enhanced the relevant theories on the causes of intestinal dysfunction in coal miners and has suggested a new approach to intervention.